Prevalence of nasal methicillin-resistant Staphylococcus aureus colonization in healthcare workers in a Western Australian acute care hospital. - Verwer, P.; Robinson, J.; Coombs, Geoffrey; Wijesuriya, T.; Murray, R.; Verbrugh, H.; Riley, T.; Nouwen, J.; Christiansen, Keryn (Springer, 2011)
Due to a longstanding comprehensive “search and destroy policy”, methicillin-resistant Staphylococcus aureus (MRSA) is not endemic in Western Australian (WA) acute care hospitals. As the prevalence of MRSA in the community has increased, healthcare workers (HCW) are at risk of importing MRSA into hospitals. We aimed to determine the prevalence of and risk factors for nasal MRSA colonization in our HCW population. A period prevalence study was conducted at an 850-bed tertiary hospital. Basic demographics and a nasal swab were obtained. A total of 1,542 HCWs employed in our centre were screened for MRSA, of whom 3.4% (n=52) were colonized. MRSA colonization was more common in patient care assistants (6.8%) and nurses (5.2%) than in allied health professionals (1.7%) and doctors (0.7%) (p< 0.01). Working in “high-risk” wards that cared for MRSA colonized/infected patients was the strongest risk factor for HCW MRSA colonization (p<0.001). ST1-IV and ST78-IV (the most common community clones in the region) were the most frequently identified clones. In conclusion, MRSA colonization of HCWs occurs primarily in HCWs caring for patients colonized or infected with MRSA. Surveillance screening of HCWs should be regularly performed on wards with patients with high MRSA colonization prevalence to prevent further spread in the hospital.